Experimental characterization of diffuse speckle pulsatile flowmetry system - Choo, Tristan Wen Jie (2023)
The recently developed Diffuse Speckle Pulsatile Flowmetry (DSPF) technique offers high measurement rates of around 300 Hz for non-invasive blood flow measurement of blood flow in deep tissue (up to a depth of approximately 15 mm), showing promising potential for the monitoring of various pathologies associated with abnormal blood flow. The effects of various parameters associated with this technique such as speckle size and exposure time on the measured flow readings, however, have yet to be studied. In this work, we examine these relationships experimentally, observing that the number of pixels per speckle (a measure of speckle size) and exposure time have a strong inverse relationship and a positive relationship respectively with the measured DSPF readings in no-flow setups using both static single light scattering and multiple light scattering mediums. We also studied how the sensitivity of DSPF readings to flow is affected by these parameters, finding that the number of pixels per speckle and exposure time have an inverse relationship and strong positive linear relationship respectively with the gradient of the regression line between the actual and measured flow rates in a dynamic setup using a tissue-mimicking flow phantom. It is hoped that these results would enable researchers using the DSPF technique to select and utilize the most optimized settings for their specific use applications.